Management of information system / Aminuddin Mohd Tahir...[et al.] - Mohd Tahir., Aminuddin; Wan Ismail, Wan Noor Azizah; Ahmad, Nor Hayati; Mohamad, Nurul Huda (1990)
This project is a partial requirement of our course. A prototyping is developed in this project. Prototyping is a pilot or test and it is expected that the prototype will be changed through several alterations.